Anti-lymphoma Activity of Averrhoa bilimbi Fruit Extract in Swiss Albino Mice - Grace, Dr. V. M. Berlin (Asian Journal of Pharmaceutics (AJP), 2016)
Aim: To evaluate the effect of Averrhoa bilimbi fruit extract against Dalton’s ascitic lymphoma (DAL) induced in Swiss albino mice. Materials and Methods: DAL cell line was injected via intraperitoneal to Swiss albino mice and was treated with A. bilimbi fruit extract for 15 days. Then, the animals were sacrificed on 15th day to test hematological parameters, body weight, and tumor volume. The in vitro growth inhibition effect of A. bilimbi fruit extract on DAL cell line was also studied using 3-(4,5-dimethylthiazol-2yl)-2,5-diphenyltetrazolium bromide (MTT) assay. Results and Discussion: The A. bilimbi fruit extract showed promising anti-lymphoma activity in Swiss albino mice. Treatment of A. bilimbi normalized the hematological parameters significantly (**P < 0.01) by decreasing the high level of white blood cell and by increasing the levels of red blood cells and hemoglobin count when compared with DAL control mice. The treated mice group with A. bilimbi fruit extract resulted in significant (P < 0.01) decrease in body weight when compared with the control. The MTT assay also has shown a significant growth inhibition percent (97.96%) for the fruit extract treatment. Conclusion: The current study revealed the anti-lymphoma activity of the A. bilimbi fruit extract against DAL cell line induced Swiss albino mice.